Pertussis Immunisation in Pregnancy Safety (PIPS) Study: A retrospective cohort study of safety outcomes in pregnant women vaccinated with Tdap vaccine. Issue 34 (16th August 2018) - Griffin, Jennifer B.; Yu, Lennex; Watson, Donna; Turner, Nikki; Walls, Tony; Howe, Anna S.; Jiang, Yannan; Petousis-Harris, Helen
Abstract: Background: New Zealand has funded the administration of tetanus, diphtheria and acellular pertussis (Tdap) vaccine during pregnancy to prevent infant pertussis since 2013. The aim of this study was to assess the safety of Tdap vaccine administered to pregnant women as part of a national maternal immunisation programme. Methods: We conducted a national retrospective observational study using linked administrative New Zealand datasets. The study population consisted of pregnant women eligible to receive funded Tdap vaccination from 28 to 38 weeks gestation in 2013. Primary study outcomes were based on prioritised adverse events for the assessment of vaccine safety in pregnant women, as defined by WHO and Brighton Collaboration taskforces. We examined the effect of Tdap vaccination on prioritised maternal outcomes using Cox proportional hazard models. Adjusted hazard ratios controlled for key confounding variables. Results: In the cohort of 68, 550 women eligible to receive funded antenatal Tdap vaccination during 2013, 8178 (11.9%) were vaccinated and 60, 372 (88.1%) were unvaccinated. The use of Tdap in pregnancy was not associated with an increase in the rate of primary outcomes, including preterm labour; pre-eclampsia; pre-eclampsia with severe features; eclampsia; gestational hypertension; fetal growth restriction; or post-partum haemorrhage. Tdap also did not increase secondary outcomes, including gestational diabetes mellitus; antenatal bleeding; placental abruption; premature rupture of membranes; preterm delivery; fetal distress; chorioamnionitis; or, maternal fever during or after labour. Lactation disorders was the only secondary maternal outcome with a significantly increased hazard ratio. Tdap vaccine had a protective effect on pre-eclampsia with severe features, preterm labour, preterm delivery, and antenatal bleeding. Conclusion: We did not detect any biologically plausible adverse maternal outcomes following Tdap vaccination during pregnancy. This study provides further assurance that Tdap administration during pregnancy is not associated with unexpected safety risks.